2020
DOI: 10.1017/aog.2020.46
|View full text |Cite
|
Sign up to set email alerts
|

Fast Ice Prediction System (FIPS) for land-fast sea ice at Prydz Bay, East Antarctica: an operational service for CHINARE

Abstract: Abstract A Fast Ice Prediction System (FIPS) was constructed and is the first regional land-fast sea-ice forecasting system for the Antarctic. FIPS had two components: (1) near-real-time information on the ice-covered area from MODIS and SAR imagery that revealed, tidal cracks, ridged and rafted ice regions; (2) a high-resolution 1-D thermodynamic snow and ice model (HIGHTSI) that was extended to perform a 2-D simulation on snow and ice evolution using atmospheric forcing fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…This parameterization allows HIGHTSI to quantitatively simulate the sub-surface melting of snow and ice (Cheng et al 2003). HIGHTSI has been extensively validated and widely applied in both process studies (Cheng et al 2008, 2013, Wang et al 2015, Merkouriadi et al 2017, Mäkynen et al 2020 and operational service for the Prydz Bay region (Zhao et al 2020). Detailed model parameterizations are given in the supporting file (table S2).…”
Section: Methodsmentioning
confidence: 99%
“…This parameterization allows HIGHTSI to quantitatively simulate the sub-surface melting of snow and ice (Cheng et al 2003). HIGHTSI has been extensively validated and widely applied in both process studies (Cheng et al 2008, 2013, Wang et al 2015, Merkouriadi et al 2017, Mäkynen et al 2020 and operational service for the Prydz Bay region (Zhao et al 2020). Detailed model parameterizations are given in the supporting file (table S2).…”
Section: Methodsmentioning
confidence: 99%
“…The formation of snow ice was simulated by Zhao et al (2020) for LFI around ZS in 2015. However, neither the ice temperature nor the HT ratio profile at ZS2015 in our study shows signs of snow ice formation, which is likely because drifting snow was 515 not considered in the sea ice model used by Zhao et al (2020) and the simulated snow depth was much larger than the observed value at ZS2015. Our buoy data did not indicate any signs of the formation of snow ice over the LFI around DS, consistent with the results presented by Heil (2006).…”
Section: Flooding and Snow Ice Formationmentioning
confidence: 99%
“…The local distribution of LFI, in some areas, can affect the formation and evolution of polynyas in its downwind region (Nihashi and Ohshima, 2015) and mechanically bond and establish vulnerable outer ice shelf margins (Massom et al, 2018). In addition, LFI plays a critical role in ice-associated ecosystems as a stable habitat for microorganisms (McMinn et al, 2000), a breeding 40 ground for seals and penguins (Massom et al, 2009), and a support ground for transportation logistics at many Antarctic stations (Kim et al, 2018;Zhao et al, 2020). A better understanding of LFI can provide valuable insights into the climate responses of Antarctic coastal systems.…”
Section: Introductionmentioning
confidence: 99%
“…As a seasonal land extension, landfast ice can be a habitat for polar animals and serves as a platform for hunting, fishing, and scientific observation (Kooyman & Ponganis, 2014). The distribution of landfast ice is also important for polar navigation and offshore exploration (Hughes et al., 2011; Zhao et al., 2020). A model without landfast ice (parameterized or resolved) will also have difficulties in simulating the processes related to landfast ice, and for example, will have polynyas in the wrong place (Itkin et al., 2015).…”
Section: Introductionmentioning
confidence: 99%